2016
DOI: 10.1038/srep37816
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Signatures of the Anterior Insula are associated with Risk-taking Tendency of Analgesic Decision-making

Abstract: In a medical context, decision-making is associated with complicated assessment of gains, losses and uncertainty of outcomes. We here provide novel evidence about the brain mechanisms underlying decision-making of analgesic treatment. Thirty-six healthy participants were recruited and completed the Analgesic Decision-making Task (ADT), which quantified individual tendency of risk-taking (RPI), as the frequency of choosing a riskier option to relieve pain. All the participants received resting-state (rs) functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…On the other hand, the cognitive control system is involved in the selection of actions, conflict monitoring, impulse inhibition, and regulation of the influence of the reward system on the decision-making process [ 36 , 50 , 52 , 84 , 87 , 107 110 ]. Gray matter volume alterations in these areas have been described in executive functioning alterations [ 111 ] and manifestations of risk behavior in both self-reported and laboratory tasks [ 106 , 109 , 112 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the cognitive control system is involved in the selection of actions, conflict monitoring, impulse inhibition, and regulation of the influence of the reward system on the decision-making process [ 36 , 50 , 52 , 84 , 87 , 107 110 ]. Gray matter volume alterations in these areas have been described in executive functioning alterations [ 111 ] and manifestations of risk behavior in both self-reported and laboratory tasks [ 106 , 109 , 112 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Koppel et al (2017) found that acute pain induction increased risk‐taking when deciding between a safe and a risky option in a gain frame; however, no differences in risk‐taking were observable in a loss frame. Lin et al (2016) showed that imagined pain relief was correlated with risk preferences in an analgesic decision‐making task. In this sense, the utility of imagining a reduction in pain from level 9 to level 6 on an 11‐point scale was negatively associated with choosing a risky treatment option.…”
Section: Introductionmentioning
confidence: 99%